Tantangan Penerapan Konsep Negara Hukum dalam Era Digital: Studi Kasus UU ITE dan Kebebasan Berekspresi: Penelitian - Raudhina Oktia Ayu (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study discusses the challenges of implementing the concept of a state based on law in Indonesia in the context of the digital era, focusing on the Electronic Information and Transactions Law (UU ITE) and its impact on freedom of expression. A state based on law requires the supremacy of law, protection of human rights, and the principle of legality. However, technological developments and the presence of the ITE Law have created tensions between legal protection and digital freedom. This study uses a qualitative approach and case studies of several legal decisions. The results show that certain articles in the ITE Law, such as Articles 27 and 28, are often used to limit individual expression, which has the potential to conflict with the principles of a democratic state based on the rule of law. This study recommends normative revisions to the ITE Law and strengthening of human rights protection mechanisms in the digital space based on the concept of a state based on the rule of law.